The Influence of ITO Dopant Density on J-V Characteristics of Silicon Heterojunction Solar Cells: Experiments and Simulations. (August 2015) - Kirner, Simon; Hartig, Manuel; Mazzarella, Luana; Korte, Lars; Frijnts, Tim; Scherg-Kurmes, Harald; Ring, Sven; Stannowski, Bernd; Rech, Bernd; Schlatmann, Rutger
Abstract: The TCO/a-Si:H(p) contact is a critical part of the silicon heterojunction solar cell. At this point, holes from the emitter have to recombine loss free with electrons from the TCO. Since tunneling is believed to be the dominant transport mechanism, a high dopant density in both adjacent layers is critical. In contrast to this, it has been reported that high TCO dopant density can reduce field effect passivation induced by the a-Si:H(p) layer. Thus, in this publication, we systematically investigate the influence of a thin (∼10 nm) ITO contact layer with dopant densities ranging from N d = 10 19 - 10 21 cm -3 placed between an ITO bulk layer of 70 nm with N d = 2·10 20 cm -3 and the a-Si:H(p) emitter on the J-V characteristics, with the aim to find an optimum N d . We accompanied our experiments by AFORS-HET simulations, considering trap-assisted tunneling and field dependent mobilities in the a-Si:H(p) layer. As expected, two regimes are visible: For low N d the devices are limited by inefficient tunneling, resulting in S-shaped J-V characteristics. For high N d a reduction of the field effect passivation becomes visible in the low injection range. We can qualitatively reproduce these findings using device simulations.